Evaluation of football players' power during a maturation period by use the RAST test - Adrian Sieroń; Dawid Gomola; Jadwiga Pietraszewska (Kazimierz Wielki University, 2017)
Abstract          Introduction: Properly planned and implemented training cycle should influence the development      of motor skills, responsible for anaerobic work. The ability to quickly achieve and maintain high power is crucial to the final success of football (Stankiewicz               i Cieślicka, 2013). Performing     a specific test several Times, during preparation for the league games, gives the coaches and instructors of the sport the ability to dispense appropriate training loads, before the start and during the game. Moreover, they can freely watching the progress of the pupil. An athlete who, under intense effort, will reach high speeds with a low power loss, will achieve a high level of tolerance to fatigue. The ability to rapidly speed up and to multiple repetition of this activity, is now the basic requirement of most sports, such as football, basketball, handball, athletics, tennis and more.          The aim of the study is to assess the power of football players of different ages with the RAST test. In addition, relative power will be tested with reference to the body weight of the subjects.         Conclusion: By analyzing the study population, it can be concluded that body mass is significantly dominant in the group of high school students, which undoubtedly influences their ability to gain more power. Furthermore, taking into account the results of the relativized power, it has to be stated, that after weight loss relative power is also significantly dominant in high school students, which is evidence for their more advanced biological development and the impact of football training on the obtained results.